Bunuh Diri dalam Tiga Novel Indonesia: Perspektif Psikologi Kematian: Suicide in Three Indonesian Novels: A Psychological Study of Death Perspective - Anas Ahmadi; Haris Supratno; Parmin Parmin (TOTOBUANG, 2022)
Abstract This study explores the suicidal desire and behavior of modern humans found in Indonesian literature. So far, research on suicidal ideation and behavior tends to be mostly done in the realm of psychology. Unfortunately, research on suicidal ideation and behavior from the perspective of the psychology of death is still not widely carried out by researchers in the field of literature. In this regard, this study raises the desire and suicidal behavior of modern humans as reflected in Indonesian literature. The method used in this research is qualitative using data sources from three Indonesian novels, Olenka, Rafilus, and Supernova. The data collection technique was carried out in a documentary manner referring to the text data contained in the novel. The data analysis technique uses the stages of identification, classification, and exposure to research data. The results of the study show the following. First, the novel Olenka, Rafilus, and Supernova depicts a character who narrates a suicide committed by another person and he feels how the suicide happened. Second, suicide is contained in the character's mind as a responsibility of human freedom. Third, suicide appears in the flash of the character's mind. Keywords:Â desire, behavior, suicide, literature, psychology of death